I/O buffer model development from IBIS and IMIC for simulation in SPICE - Wang, Ying. (2008)
In today's high-speed and high IC density digital system, many new problems have appeared. One significant issue is signal integrity (SI) which concerns signal purity. Signal noise and signal delay due to interconnect have been becoming to dominate circuit performance. In order to design reliable digital circuits, SI analysis becomes imperative.